Implementation of Public Private Partnership in The Development of Tourism in Sumenep District - Kriswibowo, Arimurti; Pramestya, Eka Arum; Prasetyo, Khusnul (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
The development of the tourism sector in Sumenep City continues to be encouraged to improve the community's economy and increase Regional Original Revenue. But unfortunately the target of foreign tourist visits can not be achieved because of the availability of inadequate infrastructure. To meet these shortcomings, the Sumenep City Government established a partnership with PT. Persada Investama Karya Utama to establish a three-star hotel "de Baghraf". This study aims to describe the implementation of the Public Private Partnership (PPP) and describe in detail the benefits and the constraints faced in the construction of the three-star hotel "de Baghraf" in Sumenep conducted by the Government of Sumenep City with PT. Persada Investama Karya Utama. This research uses descriptive qualitative research methods using PPP theory. The results of this study indicate that the collaboration carried out using the Build Own Operate (BOO) partnership scheme is following the stipulated conditions because it has fulfilled the 9 (nine) stages of the implementation of Public Private Partnership. The benefits obtained from this Cooperation are supporting the implementation of Visit Sumenep and supporting tourism development programs, profits from hotel operations, and employment. Several obstacles were encountered such as low investor interest and difficulty in finding skilled human resources.